2018
DOI: 10.1089/mdr.2017.0251
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Broth Microdilution with Polystyrene and Glass-Coated Plates, Agar Dilution, E-Test, Vitek, and Disk Diffusion for Susceptibility Testing of Colistin and Polymyxin B on Carbapenem-Resistant Clinical Isolates of Acinetobacter baumannii

Abstract: Different susceptibility testing methods for polymyxins show great variation in their results and BMD using glass-coated plates can be considered the best candidate for gold standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 23 publications
3
25
0
2
Order By: Relevance
“…These type of microtubes showed the least adsorption, followed by standard polypro-pylene and glass. Similar results have also been obtained from other studies, demonstrating that BMD with glass-coated plates gives more reliable MIC results for polymyxins than BMD with polystyrene plates (96,123). Furthermore, Karvanen et al (103) previously showed that colistin adsorption was proportionally higher at a lower concentration of 0.125 g/ml after 24 h at 35°C, with the estimated colistin concentration in MHB being 8%, 13%, and 25% in polystyrene, polypropylene, and glass-coated wells, respectively.…”
Section: Challenges In Polymyxin Susceptibility Testingsupporting
confidence: 86%
“…These type of microtubes showed the least adsorption, followed by standard polypro-pylene and glass. Similar results have also been obtained from other studies, demonstrating that BMD with glass-coated plates gives more reliable MIC results for polymyxins than BMD with polystyrene plates (96,123). Furthermore, Karvanen et al (103) previously showed that colistin adsorption was proportionally higher at a lower concentration of 0.125 g/ml after 24 h at 35°C, with the estimated colistin concentration in MHB being 8%, 13%, and 25% in polystyrene, polypropylene, and glass-coated wells, respectively.…”
Section: Challenges In Polymyxin Susceptibility Testingsupporting
confidence: 86%
“…Albur et al demonstrated that the polystyrene trays used also have an influence: using tissue-culture-coated round-bottom trays gave a 5.3-fold increase in MIC values compared to noncoated V-bottom trays [113], for the material used [106] (Table S3). A very recent study compared polystyrene coated trays to glass coated trays and also showed very few differences (Table 3) [114].…”
Section: New Recommendations On Polymyxins Susceptibility Testingmentioning
confidence: 99%
“…A number of publications have demonstrated that the results of AST of many antimicrobials, not just AMP, can be affected by the choice of laboratory plasticware for use with the broth microdilution procedure and even the choice of tubes used for preparing reagents (Singhal et al, 2018 ; Kavanagh et al, 2019 ). This also applies to AST of AMP (Otvos and Cudic, 2007 ; Wiegand et al, 2008 ; Kristensen et al, 2015 ).…”
Section: Antimicrobial Susceptibility Testing Of Ampmentioning
confidence: 99%